Polymer conformations in polymer nanocomposites containing spherical nanoparticles. Issue 2 (11th November 2014) - Karatrantos, Argyrios; Clarke, Nigel; Composto, Russell J.; Winey, Karen I.
Abstract : We investigate the effect of various spherical nanoparticles on chain dimensions in polymer melts for high nanoparticle loading which is larger than the percolation threshold, using molecular dynamics simulations. Abstract : We investigate the effect of various spherical nanoparticles on chain dimensions in polymer melts for high nanoparticle loading which is larger than the percolation threshold, using molecular dynamics simulations. We show that polymer chains are unperturbed by the presence of repulsive nanoparticles. In contrast polymer chains can be perturbed by the presence of attractive nanoparticles when the polymer radius of gyration is larger than the nanoparticle radius. At high nanoparticle loading, chains can be stretched and flattened by the nanoparticles, even oligomers can expand under the presence of attractive nanoparticles of very small size.